2009
DOI: 10.1002/aqc.1052
|View full text |Cite
|
Sign up to set email alerts
|

Eradication of colonizing populations of zebra mussels (Dreissena polymorpha) by early detection and SCUBA removal: Lake George, NY

Abstract: 1. Since their introduction to North America, zebra mussels (Dreissena polymorpha) and quagga mussels (Dreissena rostriformis bugensis) have rapidly colonized North American fresh waters. Strategies for limiting the economic and ecological impacts of zebra mussels exist, but there are few examples where once zebra mussels have invaded a natural body of water they have been removed or managed without the use of ecologically destructive methods. The first successful attempt to eradicate a colonizing population o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 43 publications
0
32
0
2
Order By: Relevance
“…Invasive fish, macrophytes, and invertebrates have been observed from small (Wimbush et al 2009) to large lake systems (Beeton 2002). Once an invasive species has been identified in a region, the primary step for researchers and resource managers is to define population extent.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Invasive fish, macrophytes, and invertebrates have been observed from small (Wimbush et al 2009) to large lake systems (Beeton 2002). Once an invasive species has been identified in a region, the primary step for researchers and resource managers is to define population extent.…”
mentioning
confidence: 99%
“…The introduction and spread of invasive species in lacustrine environments have ecological and economic impacts (Pimentel et al 2005). Invasive fish, macrophytes, and invertebrates have been observed from small (Wimbush et al 2009) to large lake systems (Beeton 2002). Once an invasive species has been identified in a region, the primary step for researchers and resource managers is to define population extent.…”
mentioning
confidence: 99%
“…In Lake Erhai, our study was the first to demonstrate that the two species showed clearly different spawning cycles within the same ecosystem outside of their native range, and this is a crucial issue for the timing of deployment of remediation actions (Ling, 2002;Britton et al, 2011). Management operations for fishes may often be most effective when implemented pre-spawning because offspring usually increase population size by several orders of magnitude and disperse extensively within the ecosystem (Knapp & Matthews, 1998;Ludgate & Closs, 2003;Wimbush et al, 2009;Britton et al, 2011). Moreover, the removal of adults soon after spawning may result in a population increase in juveniles (e.g., decreased intraspecific competition) rather than their decline.…”
Section: Discussionmentioning
confidence: 87%
“…Therefore, at sites where quagga mussels have invaded, stakeholders advocate for intensive management (or eradication) of invasive mussels. A number of current eradication efforts have reported early signs of success to manage against the novel ecosystem created by quagga mussels (Wimbush et al 2009). …”
Section: Managing Against Novel Ecosystemsmentioning
confidence: 98%